Progenitor Hematopoietic Cells Implantation Improves Functional Capacity of End Stage Coronary Artery Disease Patients with Advanced Heart Failure - Yoga Yuniadi; Yuyus Kusnadi; Lakshmi Sandhow; Rendra Erika; Dicky A. Hanafy; Caroline Sardjono; R. W. M. Kaligis; Manoefris Kasim; Ganesja M. Harimurti (Cardiology Research and Practice)
Background. Proangiogenic Hematopoietic Cells (PHC) which comprise diverse mixture of cell types are able to secrete proangiogenic factors and interesting candidate for cell therapy. The aim of this study was to seek for benefit in implantation of PHC on functional improvement in end stage coronary artery disease patients with advanced heart failure. Methods. Patients with symptomatic heart failure despite guideline directed medical therapy and LVEF less than 35% were included. Peripheral blood mononuclear cells were isolated, cultivated for 5 days, and then harvested. Flow cytometry and cell surface markers were used to characterize PHC. The PHC were delivered retrogradely via sinus coronarius. Echocardiography, myocardial perfusion, and clinical and functional data were analyzed up to 1-year observation. Results. Of 30 patients (56.4±7.40 yo) preimplant NT proBNP level is 5124.5±4682.50 pmol/L. Harvested cells characterized with CD133, CD34, CD45, and KDR showed 0.87±0.41, 0.63±0.66, 99.00±2.60, and 3.22±3.79%, respectively. LVEF was improved (22±5.68 versus 26.8±7.93, p<0.001) during short and long term observation. Myocardial perfusion significantly improved 6 months after treatment. NYHA Class and six-minute walk test are improved during short term and long term follow-up. Conclusion. Expanded peripheral blood PHC implantation using retrograde delivery approach improved LV systolic function, myocardial perfusion, and functional capacity.